2007
DOI: 10.1002/jmri.20836
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of exchange and multicomponent T1 relaxation on the short repetition time spoiled steady‐state signal and the DESPOT1 T1 quantification method

Abstract: Purpose: To examine the spoiled steady-state (spoiled gradient-recalled echo sequence [SPGR]) signal arising from two-compartment systems and the role of experimental parameters, in particular TR for resolving signal from each compartment. Materials and Methods:Using Bloch-McConnell simulations, we examined the SPGR signal from two-component systems in which T 1 is much greater than the mean residence time ( m ) of proton spins in each component. Specifically, we examined the role of TR on the ability to resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 33 publications
1
26
1
Order By: Relevance
“…Neglecting exchange between components, the two-component SPGR signal is conventionally given by (33) MSPGRk=MSPGR0sin(B1αk)true(fs1E1,s1E1,scos(B1αk)+(1fs)1E1,l1E1,lcos(B1αk)true) where the dimensionless quantity B 1 denotes an RF transmit scaling factor, s and l respectively denote the short- and long- T 2 components, f s is the fraction of the short T 2 component, M0SPGR represents the signal amplitude at echo time TE = 0 and incorporates proton density and machine factors, and α k is the k th excitation FA out of a total of K FAs. We also define E 1, j = exp (−TR SPGR /T 1, j ), where T 1, j is the spin-lattice relaxation time of the j th component.…”
Section: Theorymentioning
confidence: 99%
“…Neglecting exchange between components, the two-component SPGR signal is conventionally given by (33) MSPGRk=MSPGR0sin(B1αk)true(fs1E1,s1E1,scos(B1αk)+(1fs)1E1,l1E1,lcos(B1αk)true) where the dimensionless quantity B 1 denotes an RF transmit scaling factor, s and l respectively denote the short- and long- T 2 components, f s is the fraction of the short T 2 component, M0SPGR represents the signal amplitude at echo time TE = 0 and incorporates proton density and machine factors, and α k is the k th excitation FA out of a total of K FAs. We also define E 1, j = exp (−TR SPGR /T 1, j ), where T 1, j is the spin-lattice relaxation time of the j th component.…”
Section: Theorymentioning
confidence: 99%
“…However, authors of previous multicomponent T2 mapping studies (24)(25)(26)(27)(28) have been limited by their use of CarrPurcell-Meiboom-Gill techniques with long acquisition times, which allowed for cartilage assessment on only a single section of ex vivo specimens. Multicomponent driven equilibrium single-shot observation of T1 and T2 (mcDESPOT) is a rapid method for multicomponent T2 mapping (29)(30)(31)(32)(33)(34). The use of mcDESPOT allows acquisition of three-dimensional (3D) voxel-based measurements of the fractions and T2 values of the fast-relaxing and slow-relaxing water components of the articular cartilage of the human knee joint at 3.0 T with high spatial resolution, large volume coverage, and relatively Abbreviations: AUC = area under the curve BLOKS = Boston-Leeds osteoarthritis knee scoring CI = confidence interval F F = fraction of the fast-relaxing water component FSE = fast spin echo mcDESPOT = multicomponent driven equilibrium singleshot observation of T1 and T2 T2 F = T2 of the fast-relaxing water component T2 Single = single-component T2 T2 s = T2 of the slow-relaxing water component 3D = three-dimensional…”
Section: Study Groupmentioning
confidence: 99%
“…Results of previous studies have shown high pixelby-pixel correlation between cartilage T2 Single measurements obtained by using mcDESPOT and those obtained by using conventional Carr-Purcell-Meiboom-Gill techniques (35). Multicomponent T2 maps for the fast-relaxing water component (T2 F ) and the slow-relaxing water component (T2 S ) and maps for the fraction of the fast-relaxing water component (F F ) were created by using the two-pool mcDESPOT reconstruction method (29)(30)(31). The mcDESPOT method fits the observed spoiled gradient-echo and balanced steady-state free-precession signal at various flip angles with the use of the mathematical model described in the Appendix E1 (Fig E1 [online] …”
Section: Implication For Patient Carementioning
confidence: 99%
“…It remains unclear how this method will fare in vivo, where the ability to resolve multicomponent T 1 relaxation has been nontrivial. Recent work in this area with rapid SPGR imaging, however, has shown it may be possible to quantify multicomponent T 1 relaxation in fast relaxing species provided the repetition time satisfies the condition TR Ͻ m (20,21). We are nevertheless confident that a combination of rapid, multiangle (and perhaps multiple TR) SPGR and SSFP imaging will permit similar analysis in vivo.…”
Section: Discussionmentioning
confidence: 95%